Mapping the landscape of financial crime: A bibliometric analysis of trends and research developments - Norhamiza Ishak; Aidi Ahmi; Rini Suryati Sulong (RSIS International, 2025)
Given the dynamic nature of our digital economy and the increasing prevalence of financial crimes, we believe that scholars in this subject area could benefit from a more systematic approach to assessing the issues and research trends related to financial crimes. Thus, the main purpose of our study is to explore the current scope of research linked to financial crimes through bibliometric analysis. Using the bibliometric method, this study retrieved literature published in academic journals indexed in the Scopus database from 1992 to 2024 for analysis. Tools such as “biblioMagika,” “Open Refine,” “VOS viewer,” and RStudio Desktop were utilized to structure, clean, and extract data for the bibliometric analysis. Four research questions were ultimately addressed. This study may serve as a reference for investigative agencies, practitioners, researchers, law enforcement, government, and legal professionals to share their knowledge and experiences, including current challenges and lessons learned regarding the increasing trend of financial crimes annually.